Peningkatan Pengetahuan Remaja Putri melalui Edukasi Gizi Aplikasi Whatsapp Group - Manjilala Manjilala; Sri Wilda; Retno Sri Lestari (Media Gizi Pangan, 2022)
Nutrition education aims to encourage positive behavior changes related to food and nutrition. Knowledge about nutrition has been proven to have a positive impact on healthy food choices, so in this case proper nutrition education is needed so that the resulting behavior is positive behavior. This study aims to determine differences in the level of knowledge of iron anemia before and after providing nutrition education through the Whatsapp Group to young women at SMAN 13 Pangkep. The research design used was quasy-experimental with a one-group pre-test and post-test control design. The sample of this research was 30 female students from SMAN 13 Pangkep. Nutrition education conducted through the WhatsApp Group virtual class. The results showed that the level of knowledge of young women before virtual education (86.7%) increased to (96.7%) after virtual education was carried out through the Whatsapp Group application. The results of the analysis of the paired sample T test obtained a p value of 0.018, which means that there are differences in the level of knowledge of iron anemia before and after nutrition education through the WhatsApp Group in young women at SMAN 13 Pangkep. Education through Whatsapp Groups for young women can increase their knowledge about iron anemia so that young women avoid iron anemia